2007
DOI: 10.1016/j.biopsych.2006.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Resisting Craving During Cigarette Cue Exposure

Abstract: Background-In cigarette smokers, the most commonly-reported areas of brain activation during visual cigarette cue exposure are: the prefrontal, anterior cingulate, and visual cortices. We sought to determine changes in brain activity in response to cigarette cues when smokers actively resist craving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
248
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(272 citation statements)
references
References 77 publications
19
248
2
Order By: Relevance
“…First, it builds on initial attempts to study the regulation of responses to drug-related stimuli (34,35) that did not observe significant reductions in craving. Here, we showed that craving could be curbed effectively via a single, clinically relevant strategy that involved cognitively reinterpreting the meaning of an initially craved substance in terms that highlighted its potential longer-term deleterious effects on one's health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it builds on initial attempts to study the regulation of responses to drug-related stimuli (34,35) that did not observe significant reductions in craving. Here, we showed that craving could be curbed effectively via a single, clinically relevant strategy that involved cognitively reinterpreting the meaning of an initially craved substance in terms that highlighted its potential longer-term deleterious effects on one's health.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, initial steps have been taken toward exploring this hypothesis by showing videos depicting substance use to cigarette smokers (34) or cocaine users (35) while asking them to "resist" or "inhibit" craving, respectively. Although both studies observed activity in at least some regions associated with control, the meaning of these activations is difficult to interpret for three reasons.…”
mentioning
confidence: 99%
“…For instance, female sex was associated with activation in Cun, STG, and Put. The Cun, which subserves visuospatial attention, has been shown to be active in response to smoking cues in several previous studies of smoking cue reactivity (Brody et al, 2007;Smolka et al, 2006;Wilson et al, 2005). The function of the STG in smoking cue reactivity is unclear.…”
Section: Negative Affect and Sexmentioning
confidence: 99%
“…Thus, the neurobiology of craving has been examined principally via human neuroimaging studies. These studies have revealed that a diffuse network of brain regions is reliably engaged by drugrelated cues (for reviews, see [2][3][4][5][6]). …”
Section: Multiple Ambiguities In the Measurement Of Drug Cravingmentioning
confidence: 99%
“…It therefore remains unclear whether the increased ACC activations reflect specific differences in cravings or differences in other withdrawal-related symptoms. A review of the studies included in the meta-analysis from Sayette & Wilson [1] reveals that only four of 11 studies that assessed the relationship showed significant associations between subjective cravings and ACC activations [3][4][5][6]. Although these results do not rule out a direct relationship between ACC activations and cravings, they do not offer a strong support for this assumption.…”
mentioning
confidence: 99%